2004
DOI: 10.1002/ejoc.200400353
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Cycloproparene Series: Cross‐Conjugated π‐Extended Alkylidenecycloproparenes

Abstract: The first simple and stable cross‐conjugated π‐extended alkylidenecycloproparenes 5, 6 and 15−22 have been prepared as coloured crystalline derivatives from use of (E,E)‐1,5‐diphenylpenta‐2,4‐dienone, (E,E)‐1,5‐diarylpenta‐1,4‐dien‐3‐ones and (E,E)‐2,5‐(diarylmethylidene)cyclopentanones with the relevant 1,1‐bis(trimethylsilyl)cyclopropa[b]naphthalene. The permanent dipole moments of the compounds have been measured, and the conformational preference of the rotamers assessed. (© Wiley‐VCH Verlag GmbH & Co. KGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
0
18
0
5
Order By: Relevance
“…This suggested that the s-trans/s-cis conformation achievable by 284-286 provided a significant contribution to the polarity of these molecules. 200 A similar structural motif is shared by ferrocenyl derivatives 287-289, which have been studied by Klimova and co-workers. 201,202 A desire to explore the effects of ring strain in crossconjugated macrocycles such as 209 (Scheme 68) led to the synthesis of cyclophanes 290a-e by Tykwinski and Eisler (Scheme 95).…”
Section: Radialene Substructuresmentioning
confidence: 93%
“…This suggested that the s-trans/s-cis conformation achievable by 284-286 provided a significant contribution to the polarity of these molecules. 200 A similar structural motif is shared by ferrocenyl derivatives 287-289, which have been studied by Klimova and co-workers. 201,202 A desire to explore the effects of ring strain in crossconjugated macrocycles such as 209 (Scheme 68) led to the synthesis of cyclophanes 290a-e by Tykwinski and Eisler (Scheme 95).…”
Section: Radialene Substructuresmentioning
confidence: 93%
“…[33] Elegantere Varianten dieses allgemeinen Zugangs erscheinen nach wie vor in der Literatur, zweifellos zum Teil wegen der leichten Zugänglichkeit von Dienonen wie 45 und 47 (Schema 7). Zu jüngsten Beispielen zählen Peterson-Olefinierungen [34,35] und Reformatsky-Reaktionen. [36] Neuere Studien von West et al haben gezeigt, dass eine Olefinierung des Dienons 45 durch Addition von lithiiertem Ethoxyacetylen, gefolgt von einer Meyer-Schuster-Umlagerung, erreicht werden kann.…”
Section: Acyclische Dendralenderivateunclassified
“…In der Tat kçnnen im Fall von nucleophilen Kupplungspartnern auch p-Allylkomplexe eine Rolle spielen. (34), als Weg zum [8]Dendralen, genutzt. [26] Hinsichtlich Synthesestufenzahl und Selektivität heben sich Kreuzkupplungsmethoden positiv von den traditionelleren Zugängen in der Dendralensynthese ab, die ebenso die Bildung einer C-C-Einfachbindung umfassen.…”
Section: Acyclische Dendralenderivateunclassified
“…1 and 2, [1][2][3] have continued to provide a source of fascination 4 since their discovery in 1984, 5 not least because the various derivatives have unexpected polarities, [6][7][8] fluorescence characteristics, 9 and unusual properties. 4,10,11 Recently, we described five protocols that allow for the synthesis of an extensive series of 1-aryl-and 1-diaryl-methylidene-1H-cyclopropa [b]naphthalenes, their polarities, and the linear dependence of their cycloproparenyl 13 C NMR chemical shifts upon the Hammett σ p + constant of the remote aryl substituent. 3 We also addressed conjugated and cross-conjugated cycloproparene derivatives containing cyclopentadiene and dithiole sub-units, 12 and others with simple π bonds that enhance polarity through extended conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…3 We also addressed conjugated and cross-conjugated cycloproparene derivatives containing cyclopentadiene and dithiole sub-units, 12 and others with simple π bonds that enhance polarity through extended conjugation. 13 Despite these advances there is no recorded attempt to utilize these exocyclic alkenes in what would be a simple and straightforward synthesis of quinodimethanes from ring opening and dimerization as occurs for the parent cycloproparenes. Sterically unencumbered cycloproparenes are ring-opened by simple acids (and halogens) in what is now regarded as a highly efficient benzylation reaction that is also promoted by Ag(I).…”
Section: Introductionmentioning
confidence: 99%